Geriatrics workforce enhancement program: educational outcomes of community-based dementia caregiver conferences. Issue 12 (1st December 2020) - Dassel, Kara B.; Rupper, Rand; Supiano, Katherine; Andersen, Troy; Butler, Jorie; Telonidis, Jacqueline; Edelman, Linda S.
ABSTRACT: Providing educational interventions to informal dementia caregivers has been shown to have numerous positive outcomes including improving general well-being and quality of life as well as reducing depression, anxiety, and caregiver stress. The purpose of this study is the development, delivery, and evaluation of caregiver conferences to educate informal dementia caregivers about dementia and caregiving. We provided eight half-day conferences for informal caregivers to educate them about Alzheimer's disease and related dementias (ADRD) and make them aware of community and state resources. Demographic and program evaluation surveys including an assessment of Alzheimer's disease knowledge were administered to participants. A total of 563 community-based caregivers attended the conferences. Participants tended to be female, White, and well-educated. Evaluation surveys showed high levels of satisfaction with the training. Paired t-tests showed no significant differences in AD knowledge prior to and following the training. Although there were no statistically significant improvements in participant ADRD knowledge, participant reported satisfaction levels with the conferences were high with the agreement that their educational needs were met and that the information that they learned will help improve the care they provide to the individual(s) with ADRD.